2007
DOI: 10.1186/1471-2350-8-78
|View full text |Cite
|
Sign up to set email alerts
|

Synpolydactyly and HOXD13 polyalanine repeat: addition of 2 alanine residues is without clinical consequences

Abstract: Background: Type II syndactyly or synpolydactyly (SPD) is clinically very heterogeneous, and genetically three distinct SPD conditions are known and have been designated as SPD1, SPD2 and SPD3, respectively. SPD1 type is associated with expansion mutations in HOXD13, resulting in an addition of ≥ 7 alanine residues to the polyalanine repeat. It has been suggested that expansions ≤ 6 alanine residues go without medical attention, as no such expansion has ever been reported with the SPD1 phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…This variant was also witnessed in few of the affected subjects, in two Asian families segregating with SPD1 (Fig. 1, B1) (5). This phenotype is the second most frequent non‐syndromic syndactyly type (15) and has been regarded as a part of type I syndactyly (OMIM 185900) (3, 16).…”
Section: The Problem Of Clinical Overlap With Other Syndactyly Typesmentioning
confidence: 87%
See 2 more Smart Citations
“…This variant was also witnessed in few of the affected subjects, in two Asian families segregating with SPD1 (Fig. 1, B1) (5). This phenotype is the second most frequent non‐syndromic syndactyly type (15) and has been regarded as a part of type I syndactyly (OMIM 185900) (3, 16).…”
Section: The Problem Of Clinical Overlap With Other Syndactyly Typesmentioning
confidence: 87%
“…Finally, Malik et al (5) described two Asian SPD families and identified four distinctive clinical categories (Fig. 1):…”
Section: The Problem Of Clinical Heterogeneity: Which Syndactyly Typementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, expansion of the HOXD13 polyalanine with 6 or fewer Ala does not cause pathogenic limb malformations (Albrecht et al, 2004); indeed, 2 expansions of Ala residues did not produce clinical effects (Malik et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…SPD may show clinodactyly and/or camptodactyly of 5th finger as minor clinical variants in different families, which appear as major phenotypes in the present family. However, both camptodactyly and/or clinodactyly are not considered as the diagnostic criteria for SPD [Malik et al, 2006, 2007; reviewed in Malik and Grzeschik, 2008]. Camptodactyly of mesoaxial toes, ulnar deviation of 3rd fingers and bifid hallux are also not the characteristics of SPD but are prominent in this kindred.…”
Section: Clinical Reportmentioning
confidence: 99%